Cooperation for a peaceful and sustainable world - Junsheng, Li; Bo, Chen; Na, Hou (Contributions to conflict management, peace economics and development ;, 2013)
Part 2 of the Cooperation for a peaceful and sustainable world volume, brings together some of the leading researchers on peace science. Chapters discuss issues including, but not restricted to, military expenditure and economics in China, India and Pakistan, Peace science in South East Asia, and approaches to anti-terrorism.